2019
DOI: 10.1029/2019jd030554
|View full text |Cite
|
Sign up to set email alerts
|

On the High‐Energy Spectral Component and Fine Time Structure of Terrestrial Gamma Ray Flashes

Abstract: Terrestrial gamma ray flashes (TGFs) are very short bursts of gamma radiation associated to thunderstorm activity and are the manifestation of the highest‐energy natural particle acceleration phenomena occurring on Earth. Photon energies up to several tens of megaelectronvolts are expected, but the actual upper limit and high‐energy spectral shape are still open questions. Results published in 2011 by the AGILE team proposed a high‐energy component in TGF spectra extended up to ≈100 MeV, which is difficult to … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 50 publications
2
22
0
Order By: Relevance
“…The distance bin size is chosen so that the circular area, corresponding to each bin, is constant and equal to 125,664km 2 . In agreement with Cummer et al (), Collier et al (), and Marisaldi et al (), most TGFs are detected within ∼500 km from the subsatellite point, and very few TGF are detected farther away than 800 km. The red WWLLN distribution is not flat due to the nonconstant latitude distribution of the WWLLN detections and AGILE's orbital inclination angle.…”
Section: Resultssupporting
confidence: 91%
“…The distance bin size is chosen so that the circular area, corresponding to each bin, is constant and equal to 125,664km 2 . In agreement with Cummer et al (), Collier et al (), and Marisaldi et al (), most TGFs are detected within ∼500 km from the subsatellite point, and very few TGF are detected farther away than 800 km. The red WWLLN distribution is not flat due to the nonconstant latitude distribution of the WWLLN detections and AGILE's orbital inclination angle.…”
Section: Resultssupporting
confidence: 91%
“…Those high energy counts are however a product of pileup, which affects short and high‐fluence events. The analysis reported in Marisaldi et al () shows that these events are still compatible with a standard RREA spectrum, with maximum energy of few tens of MeV, provided that the instrumental effects are carefully accounted for. However, the events affected by pileup are real TGFs and reliable in all other aspects; they should just be considered carefully when calculating the energy spectra.…”
Section: Resultsmentioning
confidence: 64%
“…Remarkably, WI TGFs tend to have higher values of count rate: This is explained by the shorter duration of WI events, as explained in Connaughton et al () and L20. Energies greater than 30 MeV can be either due to real photons, pileup (Marisaldi et al, ) or the presence of counts from cosmic rays, and confirm the need of relaxing the criteria on maximum energy. This led to the introduction of an additional, empirical criterion, as a way to remove even more false events: for count rate below 50 kHz, we only allow events with maximum energy up to 30 MeV.…”
Section: Methodsmentioning
confidence: 84%
“…The electronics simulation includes the effects of deadtime, pileup and pileup rejection, and preamplifier resets, so it simulates the paralysis in the peak of the TGF. The need to pay careful attention to instrumental deadtime in TGFs has been known for a while, but the importance of including the effects of pileup has become clearer more recently, particularly in the reanalysis of AGILE data by Marisaldi et al (2019), which demonstrated that an apparent extra high-energy component in the spectrum could be explained by pileup and deadtime issues. Their procedure was similar to the multistage simulation outlined here.…”
Section: Simulation Proceduresmentioning
confidence: 99%